The establishment of constitutive model in the cutting simulation of tool design for cast iron material - Xian Wu; Zhiqin Su; Chao Zhang; Xuefeng Zhao; Hongfei Yao; Yuan Li; Feng Jiang (Journal of Materials Research and Technology)
The PCBN tools are the most suitable tool to machine the cast iron materials, which is the main material to produce brake discs in the various vehicles. The cutting simulation is the most cost-effective and widely used method to obtain the optimal tool geometric design. The constitutive model of workpiece material is the foundation of the cutting simulation for tool design. In this paper, the constitutive models of cast iron material are tested with various test methods, include the split Hopkinson pressure bar test, the thermophysical test and turning experiments. Based on the constitutive model of cast iron, the cutting simulation model was established and verified, the simulation error is within an acceptable range of less than 10.80 %. By the application of the cutting simulation, the optimal cutting edge geometric design of PCBN tool for machining of cast iron was obtained, the cutting edge radius of 30 μm, the chamfer width of 10 μm and chamfer angle of 15°. The research results can offer an important guideline to tool design for machining of cast iron materials.